Evaluating the Assessment System of Basic Courses in the Department of Electrical Engineering - Edy Supriyadi; Sunaryo Soenarto; Faranita Surwi; Eko Prianto (Jurnal Pendidikan Teknologi dan Kejuruan, 2017)
This study aimed to examine the assessment system of the students’ learning outcomes in the basic courses of engineering at Electrical Engineering Education Program, Faculty of Engineering UNY. The investigation included the aspects of planning, implementation, and outcomes. This was an evaluation study which employed a countenance-stake evaluation model. Its main concern was the assessment system of students’ learning outcomes in engineering basic courses at Electrical Engineering Education Program, Faculty of Engineering UNY, including the aspects of planning (antecedent), implementation (transaction), and outcomes (outcomes). The results showed that: (1) the antecedent aspect was noticeably quite good, (2) the transaction aspect was categorized as good and quite good by the lecturers and the students respectively, (3) the outcomes aspect was categorized as quite good both by the lecturers and the students.